Governing the sewage treatment plant in Malaysia: A case study at Klang Valley - Mariyappan, Raman; Ismail, Hamidi; Syed Hussain, Tuan Pah Rokiah; Sathivelu, Muttamah (2020)
Governing the level of sustainable green practices (energy efficiency, indoor environmental quality, sustainable site planning & management, materials & resources, water efficiency and innovation) among developers is indeed an aspect that needs immediate attention in the nonresidential projects in the Klang Valley, Malaysia. Sustainable green practices promote positive activities that will ensure energy efficiency, water efficiency, fairness, effectiveness, divergence, less disparity, less discrimination, reduced cost, reasonable pricing, pleasant design, serenity, mutual comfort and many other characteristics in the future of the construction industry. The developers must converge at a point where no one is short changed due to limitations in the implementation mechanism of sustainable green practices in the nonresidential projects. The aim of this research is to investigate the extent of sustainable green practices in the Pantai 2 Sewage Treatment Plant. In order to achieve the research aims, the specific objectives of this research are divided into the following sequential steps: identification of the existing sustainable practices implemented in the Pantai 2 Sewage Treatment Plant; Model, assess and compare against common benchmarks the Energy Efficiency for the administrative building; Model, assess and compare against common benchmarks the Water Efficiency for the administrative building; and assessment of the replicability of the sustainable practices for other Sewage Treatment Plants. Quantitative and qualitative research methods were used, in which a total of 381 public respondents, selected through systematic random sampling, were employed and a total of eight organizational samplings were used. Briefly, the result shows evidence of an existing level of energy efficiency, solar power panels for the parking bays, water efficiency from rain water harvest and the utilization of eco-park for public activities. Surprisingly, 87 percent of the respondents reported not being aware of the existence of the underground sewage treatment plant at Pantai 2 Sewage Treatment Plant